Role of Ayurveda in the Management of Ardhav bhedak W.S.R to Migraine – A Review - Gautam, Meenakshi; Mishra, Pramod Kumar (International Research Journal of Ayurveda & Yoga, 2023)
Background: The most frequent neurological condition for which patients seek medical care is headache, which globally causes more disability than any other neurological condition. Migraine, commonly referred to as “Hemicrania,” which means “half of the head,” is the second most frequent primary headache. Vomiting, nausea, and sensitivity to scent, light, or sound are all associated symptoms. Although it is not a fatal condition, it can seriously disrupt the patient’s life, necessitating greater care and attention throughout therapy. Unfortunately, only symptomatic drugs, many of which have significant side effects and can lead to dependence, have been stabilized for migraine prevention to date. Materials and Methods: The information employed in the current analysis came from both primary and secondary sources, specifically literature studies of important ayurvedic scriptures and Samhitas as well as frequently read research articles. Results: Some medication that is mentioned in the ayurvedic classics has been gathered to treat this disease. Discussion: In Ayurvedic texts there are several types of Shiro Rogas (head disorders) described by Acharyas. Amongst them the clinical features of Ardhavabhedaka are very much similar to Migraine. This review demonstrates how effective ayurveda is in treating migraines without a lot of negative effects.